Cover Image, Volume 55, Number 10, October 2020. Issue 10 (15th September 2020) - He, Zonglin; Wu, Huailiang; Zhang, Siyu; Lin, Yuchen; Li, Rui; Xie, Lijie; Li, Zibo; Sun, Weiwei; Huang, Xinyu; Zhang, Casper J. P.; Ming, Wai‐kit
Abstract : Cover Caption: The cover image is based on the Review The association between secondhand smoke and childhood asthma: A systematic review and meta‐analysis by Zonglin He et al., https://doi.org/10.1002/ppul.24961 .